Penerapan Decision Support System Beasiswa Berprestasi pada Sekolah Menengah Kejuruan - I Gusti Ayu Agung Mas Aristamy; Zain Alaik (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Every educational institution provides scholarships that are offered to its students with specified requirements, as well as at SMK Negeri 1 Sukawati. Students who receive scholarships are students who meet the requirements and criteria that have been determined. The criteria determined are report cards, absenteeism, achievement, organizational involvement, and violations. However, some problems arise when determining the prospective recipients of achievement scholarships at SMKN 1 Sukawati, particularly many students who have achievements outside of school activities or non-academic achievements do not get scholarships. One of the criteria-set is to have achievement, which means achievement is not only academic achievement but also non-academic. The design of a system that can provide recommendations to decision makers is needed, so that it is right on target in providing opportunities for students who meet the criteria considered. The Simple Additive Weighting (SAW) method is used in this study because it can choose the best alternative from several alternatives. The results obtained in this study in the form of ranking and then make a recommendation to receiving a scholarship.